2018
DOI: 10.1177/1082013218803263
|View full text |Cite
|
Sign up to set email alerts
|

Progressive freeze concentration of skimmed milk in an agitated vessel: Effect of the coolant temperature and stirring rate on process performance

Abstract: Article Number: 803263 Thank you for choosing to publish with us. This is your final opportunity to ensure your article will be accurate at publication. Please review your proof carefully and respond to the queries using the circled tools in the image below, which are available by clicking ''Comment'' from the right-side menu in Adobe Reader DC.* Please use only the tools circled in the image, as edits via other tools/methods can be lost during file conversion. For comments, questions, or formatting requests, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 36 publications
9
33
0
Order By: Relevance
“…These high final TBC retention values by FC indicate the important concentration role at subzero temperatures to obtain a liquid fraction rich in solutes and bioactive compounds in comparison to thermal technology. The values are comparable to those reported by Orellana‐Palma et al with CBFC in blueberry juice and Correa et al with falling‐film FC in aqueous coffee extract, which reported bioactive compound retentions from 80 % to 95 %, and 90%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These high final TBC retention values by FC indicate the important concentration role at subzero temperatures to obtain a liquid fraction rich in solutes and bioactive compounds in comparison to thermal technology. The values are comparable to those reported by Orellana‐Palma et al with CBFC in blueberry juice and Correa et al with falling‐film FC in aqueous coffee extract, which reported bioactive compound retentions from 80 % to 95 %, and 90%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, FC process has reached concentration levels between 30 and 60 °Brix, without affecting different quality properties in the final cryoconcentrate due to the concentration process occurs at subzero temperatures (Amran et al, 2016). Hence, different FC processes are available today: (i) suspension FC (SFC) (Ding et al, 2019), (ii) progressive FC (PFC) (Muñoz et al, 2019), (iii) falling-film FC (FFFC) (Moreno et al, 2015) and (iv) block FC (BFC) (Jin et al, 2017). In BFC, the aqueous solution is completely freezing; thawing that frozen solution, and later, the unfrozen liquid fraction (cryoconcentrate) is separated from the ice fraction by natural gravitational method or by adding external forces to improve the separation efficiency and other process parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, three CC procedures are available at industrial, semi-industrial and laboratory level: (i) suspension (SCC) [7], (ii) progressive (PCC) [8,9], and (iii) block cryoconcentration (BCC) [10]. In BCC, a liquid solution is completely freezing; then the block is thawed and, finally, the cryoconcentrate is separated from the ice fraction.…”
Section: Introductionmentioning
confidence: 99%